Is Bigger Really Better? Obesity Among High School Football Players, Player Position, and Team Success. (October 2013) - Skinner, Asheley Cockrell; Hasty, Stephanie E.; Turner, Robert W.; Dreibelbis, Mark; Lohr, Jacob A.
Objective . American football is one of the most common high school sports in the United States. We examine obesity among high school football players, and variations based on positions, team division, and team success. Patients and methods . We used 2 data sets from the North Carolina High School Athletic Association (n = 2026) and MaxPreps (n = 6417). We examined body mass index, calculated using coach-reported height and weight, by player position, division, and success based on win–loss percentage. Results . Most players (62%) were skill players, with 35% linemen and 3% punters/kickers. Most skill players (62%) were healthy weight and 4% obese or morbidly obese. In contrast, only 8% of linemen were healthy weight, with 21% morbidly obese. Team success was correlated with size only for skill players. Conclusions . Obesity is a significant problem for high school football players. Pediatricians should consider the context of football playing in assessing long-term health risks for these young men.